THE EMPLOYEE PERFORMANCE IMPACTED BY COMPENSATION AND WORK ENVIRONMENT IN OF ELEMENTARY PRIVATE SCHOOL IN GRESIK - Farida, Nur (SYNTIFIC, 2025)
Background. Organizations are required to consistently transform in order to achieve work effectiveness and efficiency. One of the fundamental aspects in supporting organizational success is the existence of quality human resources. Research Purpose. To investigate the effect of work environment and compensation on employee performance. Research Method. This research used a cross-sectional design at an elementary private school in Gresik City with 69 questionnaires. The technic sampling was used saturated sampling of teachers and employees. Data analysis used the statistical t-test. Findings. Compensation with a computed t value of 6.427> t table of 1.668 with a significance level of 0.000, and the hypothesis is accepted. According to the partial test findings (t-test) from the analysis of the study debate. Employee performance is, therefore, somewhat impacted by compensation. 2) The hypothesis is supported since the work environment has a t value of 6.175>t table of 1.668, a significance level of 0.000.Human resources performance is therefore influenced by the work environment to some extent. 3) Although the simultaneous test results (F test) indicate that Fcount 165.913> (3.14). Conclusion. Teachers' and employees' performance is simultaneously impacted by the variables of work environment and compensation.